Reporting and representation of participant race, ethnicity, and sex in pediatric IBD clinical trials - Yunlin Jiang; Jiaying Tan; Long Qin; Mingye Zhao; Zhenyi Wang (Inflammatory Bowel Diseases, 2026)
Abstract Background and Aims Pediatric inflammatory bowel disease (IBD) incidence is rising among racial and ethnic minority children, yet to our knowledge no comprehensive evaluation of demographic representation in pediatric IBD trials exists. We systematically evaluated the reporting and representation of race, ethnicity, and sex in pediatric IBD clinical trials, stratified by Crohn disease (CD) and ulcerative colitis (UC). Methods We performed a cross-sectional study of pediatric IBD trials identified in PubMed and EMBASE through March 2026. Reference distributions were derived from the National Patient-Centered Clinical Research Network (race/ethnicity, United States) and the Global Burden of Disease Study 2023 (sex, global). Enrollment incidence ratios (EIRs) were used to compare trial enrollment to expected disease burden. Comparisons were performed with random-effects meta-analyses that pooled trial-level estimates, with subgroup analyses, sensitivity analyses, and meta-regression analyses. Results Of 145 trials enrolling 8273 children, sex and race were consistently reported; ethnicity reporting rose from 0% before 2000 to 87.5% after 2020. Female participants were underrepresented (EIR, 0.91; 95% CI, 0.87-0.95), most markedly in CD trials (EIR, 0.82; 95% CI, 0.78-0.88). Black (EIR, 0.55; 95% CI, 0.42-0.71) and Hispanic (EIR, 0.46; 95% CI, 0.28-0.76) participants were underrepresented. Asian/Pacific Islander participants were overrepresented (EIR, 1.78; 95% CI, 1.37-2.30), while White and non-Hispanic participants were proportionally represented. Meta-regression showed gains over time for Asian/Pacific Islander, female, and Hispanic participants, but a slight decline for Black participants. Conclusions Female and Black children remain persistently underrepresented in pediatric IBD trials relative to disease burden; findings for Hispanic children were similar but based on a small number of trials. Enforceable diversity action plans and standardized demographic reporting are urgently needed to ensure equitable therapeutic benefit.